2017
DOI: 10.1186/s40673-017-0071-9
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in cerebellar lesions: a logit model based on neuropsychological testing

Abstract: BackgroundDamage to the cerebellum may lead to motor dysfunctions, but also to the neuropsychological deficits that comprise the Cerebellar Cognitive Affective Syndrome (CCAS). It can affect executive functions, attention, memory, visuospatial functions, language, and emotions. Our goal was to determine which neuropsychological tests could be effectively used to identify this syndrome during a short examination.MethodsTwenty-five patients with an isolated cerebellar lesion and 25 matched healthy controls were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 45 publications
1
21
0
2
Order By: Relevance
“…Consistent with their study, our finding of positive correlation with ALFF in the SFG and putamen demonstrated that the spontaneous activity within these regions decreased as the executive dysfunction progresses. Additionally, the involvement of cerebellum in the executive functions has been well established 50 52 , and the interconnection between the cerebellum and the prefrontal cortex plays an important role in the pathogenesis of executive function impairment 50 , 53 . In the present study, the negative correlation between the ALFF in the Crus I of cerebellum and Executive Function sub-score might be a reflection of the cerebellar compensatory effect to maintain the executive function in patients with FOG.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with their study, our finding of positive correlation with ALFF in the SFG and putamen demonstrated that the spontaneous activity within these regions decreased as the executive dysfunction progresses. Additionally, the involvement of cerebellum in the executive functions has been well established 50 52 , and the interconnection between the cerebellum and the prefrontal cortex plays an important role in the pathogenesis of executive function impairment 50 , 53 . In the present study, the negative correlation between the ALFF in the Crus I of cerebellum and Executive Function sub-score might be a reflection of the cerebellar compensatory effect to maintain the executive function in patients with FOG.…”
Section: Discussionmentioning
confidence: 99%
“…2 Verbal Fluency test is designed to assess the component process of executive functioning. The examinee is asked to say words that begin with a specific letter (phonemic fluency) or words that belong to a designated semantic category (semantic fluency) within time-constrained (3,(22)(23)(24).…”
Section: Resultsmentioning
confidence: 99%
“…The test is meant to assess visual scanning, number sequencing, and number-letter switching. TMT A and TMT B are to assess the speed of processing, while TMT B minus TMT A is to assess the executive functioning (3,22,23,25,26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, uncharacteristic emotional features resulting from cerebellar damage have been noted such as disinhibited behavioral responses and impulsivity in a patient with a right cerebellar infarction [ 9 ], stubbornness, thought rigidity, and inappropriate behavior (e.g., indecent humor) in patients with right-sided cerebellar lesions [ 7 ], and blunted emotional affect, social withdrawal, and low motivation in patients with left-sided cerebellar lesions [ 7 ]. In an extension of these clinical data, one study inferred that patients with cerebellar lesions may have a poor comprehension of their own emotional state because they did not report mood symptoms that they were observed to exhibit [ 10 ]. Some data suggest that cerebellar damage occurring earlier in life may result in more readily apparent emotion deficits by impacting normative growth processes such as social development and communication [ 11 ].…”
Section: Introductionmentioning
confidence: 99%